Colegio inclusivo en Puente Piedra propuesta de remodelación y ampliación de la I.E. “Augusto B. Leguía” - Siu Maldonado, Juan Franco (2022)
The project was born from the questioning about the scarcity of inclusive schools and the lack of infrastructure that should adapt to the needs of all students, including people with physical, sensory, and intellectual disabilities. The educational project is based on the idea of generating a succession of articulated spaces that establish degrees of intimacy, from the most private (classroom) to the most public (street), protecting the safety of the students and allowing the school to connect with the context at the same time. The spaces enrich each other spatially and programmatically, allowing learning to expand throughout the educational center and its surroundings. Under this premise, the school connects with the city by extending its program by cultural equipment and recreational spaces that encourage social dynamics and generate a safer environment. The school also responds to the collaborative learning strategy. The spaces are designed to promote inclusion, interaction, and the construction of knowledge and experiences. At the same at the same time, architecture looks to influence positively in the development, behavior and wellbeing of the student.